Undocumented Domestic Workers and Coronavirus Disease 2019: A Qualitative Study on the Impact of Preventive Measures - van den Muijsenbergh, Maria; Torensma, Marieke; Skowronek, Nathalia; de Lange, Tesseltje; Stronks, Karien (Frontiers in Communication, 2022)
This article describes the impact of coronavirus disease 2019 (COVID-19) preventive measures on the undocumented migrant domestic workers in the Netherlands. Undocumented migrants (UDMs) are likely to experience inequalities due to the COVID-19 pandemic. They rely on the informal market for work and housing and are usually not entitled to a healthcare insurance. However, they are not represented in the COVID-19 registrations or surveys. In order to advise the policymakers and healthcare professionals on how to tailor the preventive activities in handling a pandemic, including vaccination strategy, to the needs of this group, an insight into their experiences is needed. In our qualitative study, two focus group discussions were held with 14 UDMs, recruited through a snowball technique. The UDMs perceived the COVID-19 as a threat. Their precarious position affected their perceived vulnerability, which motivated them to seek information on and comply with preventive measures and testing. However, structural barriers decreased their self-efficacy and opportunity to comply. The COVID-19 measures impacted the lives of UDMs on essential domains, resulting in job, food, and housing insecurity, and increased barriers in access to healthcare. An intersectoral approach addressing health communication, access to healthcare, and social support, as well as legal rights for safe employment, is needed to alleviate the impact of the measures on UDMs.